Clinically actionable strategies for studying neural influences in cancer - Demir, Ihsan Ekin; Reyes, Carmen Mota; Alrawashdeh, Wasfi; Ceyhan, Güralp O.; Deborde, Sylvie; Friess, Helmut; Görgülü, Kivanc; Istvanffy, Rouzanna; Jungwirth, David; Kuner, Rohini; Maryanovich, Maria; Na’ara, Shorook; et al. (Cancer cell, 2020)
Neuro-glial activation is a recently identified hallmark of growing cancers. Targeting tumor hyperinnervation in preclinical and small clinical trials has yielded promising antitumor effects, highlighting the need of systematic analysis of neural influences in cancer (NIC). Here, we outline the strategies translating these findings from bench to the clinic.
Gesehen am 08.09.2020